Concise atlas of the world (Dorling Kindersley Pub., 2008)
From the boundaries of the Balkan states to the icy terrain of Antarctica, this book includes over 400 maps created with the digital mapping techniques and satellite data. It contains fact files on 193 nations, including each region's land use, industrial activities and population distribution.